Composition and antimicrobial activity of essential oil and Hexane-ether extract of Tanacetum santolinoides(DC.) Feinbr. and Fertig - El-Shazly, Assem; DoraI, Gamal; Wink, Michael (Zeitschrift für Naturforschung. C, a journal of biosciences, 2014)
The essential oil of the aerial parts of Tanacetum santolinoides was analyzed by capillary GLC and GLC-MS. Altogether 30 components were identified. The main constituents were thymol (18%), trans-thujone (17.5%), trans-chrysanthenyl acetate (13.2%), cis-chrysanthenyl acetate (9.2%), umbellulone (9.7%) and 1,8-cineole (4.7%). Similar essential oil pattern in addition to palmitic acid methyl ester, palmitic acid, stigmasterol, sitosterol and two flavonoidal aglycons were found in the n-hexane-ether extract. The oil showed strong in vitro activity against E. coli, Bacillus subtilis and Candida albicans.
Gesehen am 06.10.2017